KEMAMPUAN PENALARAN MATEMATIKA MAHASISWA DALAM PEMBELAJARAN MATEMATIKA SD YANG BERKONTEK NALARIA - Samsul Hadi; Ahmad Dedi Marzuki (LPPM Institut Pendidikan Nusantara Global, 2021)
The purpose of this study was to describe the mathematical reasoning ability of students in elementary mathematics learning in the context of reasoning. This research approach is a case study-based qualitative research approach with 35 PGSD students in the first semester of the 2021-2022 academic year consisting of 12 female students and 23 male students. Data was collected by means of tests and non-tests (interviews, observations, questionnaires, and documentation studies). The results showed that the mathematical reasoning ability of PGSD students in elementary mathematics learning with a context in the good category.